Precise surface patches on active particles of arbitrary shape through microstenciling - Kendra M. Kreienbrink; Zoe A. Cruse; Alisha Kumari; C. Wyatt Shields (Nature Communications)
Abstract Active particles, which locally dissipate energy from their environment to function, are useful across disciplines given their dynamic and programmable behaviors. Altering particle shape or surface asymmetry has led to advancements in controlled locomotion or collective behavior for diverse applications such as microrobotics or biomedicine. However, making arbitrary active particles of precise shape and surface composition remains a significant challenge due to limitations in conventional fabrication methods. This paper introduces a fabrication technique that combines two-photon lithography with sacrificial stencil masking to deposit arbitrary metallic patches onto particles of any shape with a limit of resolution as low as 0.2 µm. Using this method, we demonstrate three varieties of active particles displaying nonconventional dynamics: electrokinetic active spheres with tunable three-dimensional motions, catalytic microdiscs with chiral axial spinning, and steric magnetic particles forming self-limiting microrobots. Overall, this high-resolution microstenciling technique offers a versatile strategy to create well-defined active particles and microrobots for numerous practical uses.